Faktor-Faktor Yang Mempengaruhi Intensi Pembelian Do Spices - Aldo Wijaya; Richard Andrew (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Do Spices is an SME that produces dry marinade spices for proteins. However, the purchase intention for Do Spices has declined based on sales data from January to February 2024. Therefore, it is necessary to identify the factors influencing consumer purchase intentions so that Do Spices sales can increase again. Utilitarian and hedonic values are factors that can influence purchase intention. Hence, this study aims to test the significance of utilitarian and hedonic values on purchase intention, specifically among Do Spices consumers who bought between January and February 2024 through the Shopee app. This study uses a descriptive quantitative research design, with questionnaires distributed online, and data analysis conducted using SmartPLS version 3 and SPSS version 27. The results of the study indicate that utilitarian and hedonic values positive significantly influence the purchase intention of Do Spices.